Comparative analysis of mercenary in international documents and criminal acts criminalizing warfare abroad in the Criminal Code of the Republic of Serbia - Mutavdžić, Ana (NBP. Nauka, bezbednosti, policija, 2023)
Mercenary in wars and other armed conflicts, as a social phenomenon, does not stop intriguing both in moral, legal and financial terms, from the first armed conflicts until today. Although mercenary has been present practically throughout the entire human history, the regulation of mercenary activity from the aspect of international law as well as national legislation was completely neglected until recently. It was only after the Second World War that the first international documents were created that tried to define and identify mercenaries as a serious threat to international security. Much later, the norms of national (criminal) legislation began to treat mercenary as a criminal act, that is, mercenaries as criminals.Accordingly, in this research work the author will try to answer several, today more than ever, current problematic issues, which are based on the harmonization, that is, the non-harmonization of the norms regulating the field of mercenary in the acts of international law and our national criminal legislation, which tried to regulate the field of mercenary work within the national framework – with amendments to the Criminal Code from 2014.
Keywords: mercenary, mercenaries, Convention against the Recruitment, Use, Financing and Training of Mercenaries, Criminal Code of the Republic of Serbia, participation in war or armed conflict in a foreign country.